2004
DOI: 10.1210/en.2004-0330
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Regulation of Hepatic Scavenger Receptor Class BI

Abstract: High-density lipoprotein mediates a normal physiological process called reverse cholesterol transport. This process enables the transfer of cholesterol from peripheral tissues to the liver for further metabolism and eventual secretion in the form of bile. The scavenger receptor of the B class (SR-BI), human homolog of SR-BI, and CD36 and LIMPII analogous-1 (CLA-1) are different names for the same receptor that facilitates hepatocellular uptake of cholesterol from high-density lipoprotein. The pivotal role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
4
16
0
Order By: Relevance
“…And, in a series of studies, we demonstrated that PI3-kinase is essentially required for the induction of phase II detoxifying enzymes (Kang et al, 2000(Kang et al, , 2001(Kang et al, , 2003a. Signaling pathways downstream of PI3-kinase affect cell growth, survival, and motility, and IR-HCCs treated with IGF-1 showed transient PI3-kinase activation, which is consistent with previous studies (Cao et al, 2004). Either chemical inhibition or p85 subunit transfection suppressed C/EBP␤ activation and GST␣ expression by IGF-1 in IR-HCCs.…”
Section: Discussionsupporting
confidence: 91%
“…And, in a series of studies, we demonstrated that PI3-kinase is essentially required for the induction of phase II detoxifying enzymes (Kang et al, 2000(Kang et al, , 2001(Kang et al, , 2003a. Signaling pathways downstream of PI3-kinase affect cell growth, survival, and motility, and IR-HCCs treated with IGF-1 showed transient PI3-kinase activation, which is consistent with previous studies (Cao et al, 2004). Either chemical inhibition or p85 subunit transfection suppressed C/EBP␤ activation and GST␣ expression by IGF-1 in IR-HCCs.…”
Section: Discussionsupporting
confidence: 91%
“…These studies indicate that cellular migration is most impaired by changes in intracellular cholesterol content, whereas the contractile response to angiotensin II is affected by TG accumulation. receptor in fibroblasts (65) and HepG2 cells (16), we expected it to be reduced. No changes in protein content of this receptor were observed; however, we examined it after 7 days, and studies in fibroblasts and hepatic cells were done after shortterm exposure to IGF-1.…”
Section: Discussionmentioning
confidence: 97%
“…SR-BI mediates the high affinity binding of HDL and the selective uptake of HDL-derived lipids into cells (28). It has been shown in in vitro studies with the human hepatoma cell line HepG2 that IGF1 downregulates the expression of SR-BI (29). Thus, it is possible to speculate that a reduction in circulating IGF1 levels may result in the upregulation of SR-BI leading to an increased HDL-C uptake by the liver and a decrease in circulating HDL-C concentration.…”
Section: Discussionmentioning
confidence: 99%